Visual Culture (2010)
The article proposes the term “Visual Culture” as a concept that provides a wide range of contents prone for interpretation in historical researches. In the introduction, the author analyzes and justifies the concept itself, as well as its scope as a useful instrument for investigators, emphasizing on its applicability for studying, evaluating and understanding images, while revealing that all visual culture responds to theparticular interests of a managing elite and it is aimed to a specific social group or human settlement. Then, based on three well-known periods of Colombian history (pre-Hispanic times, the Colony and the Independence), the author demonstrates this hypothesis.